Unlocking the bureaucrat's Kingdom : (Brooking Institution Press, 1998)
Japan today is caught up in chronic economic crisis, its financial system wracked by record-breaking bankruptcies and its companies hobbled by bad balance sheets, overproduction, and weak consumer demand. In turn, Japan's faltering fortunes have sent shock waves across Asia, triggering the collapse of economies in South Korea, Thailand, and other Asian countries that followed its model for rapid growth and development